The Centre of Islamic Civilization in Jambi City as A Learning Resource: A Historical and Educational Analysis - Madyan, M; Bafadhal, Izhar; Damanik, Jainab Rayanti (Al'ulum Jurnal Pendidikan Islam, 2026)
The center of Islamic civilization in Jambi City is not merely a legacy of the past requiring preservation, but also a strategic educational asset for Islamic education. A historical analysis of these centers is essential to understanding the trajectory of Islamic educational development in the region. This study aims to identify the centers of Islamic civilization in Jambi City that can serve as learning resources and to determine their practical application within the framework of Islamic education. Employing a literature study method, this research analyzes historical records and academic works related to Jambi’s Islamic heritage. The findings indicate that these sites can be effectively integrated through curricular approaches, extracurricular activities, and the development of specialized learning media. Utilizing Islamic historical sites through a contextual approach makes the learning process more meaningful, interactive, and relevant to contemporary life. Ultimately, the utilization of these centers supports cultural preservation and strengthens the Islamic and national identity of the younger generation. Therefore, it is recommended that educators and policymakers optimize these historical assets to foster a deeper connection between students and their local Islamic heritage.